Morpho biochemical Assessment of Kidney Damage During Chronic Alcohol Intoxication - Khamroev I. S; Khamdamov I.B (Genius Journals, 2024)
Chronic ethanol intoxication leads to a noticeable increase in the morphometric parameters of parts of the nephron of the kidneys. At 12 months of age during the experiment, the greatest increase in the diameter of the glomerulus (19.8%), the thickness of the Shumlyansky-Bowman capsule (29.1%) and the collecting ducts (25.9%) occurs. The use of polaren syrup slightly reduces the dilated lumen of the tubules, selectively affecting the morphometric parameters of the glomerulus and nephron capsule.
Keywords: alcohol; kidneys; polaren